Pengaruh Peran Direksi Perempuan Dalam Memoderasi Hubungan Corporate Social Responsibility Terhadap Tax Avoidance (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2020 – 2023) - Sisferdi Cahya; Wahyu Meiranto (Diponegoro Journal of Accounting, 2025)
This study aims to determine the effect of role of women's direction as a moderating in relationship between corporate social responsibility on tax avoidance in manufacturing companies. This study uses internal control and audit quality as independent variables and tax avoidance measured through ETR as the dependent variable. CSR is measured through social scores and environmental scores and the role of women's direction is measured by the number of women's directions in a company. The population used in this study were manufacturing sector companies listed on the IDX. Through the purposive sampling method, there were 171 data used as the final sample in this study. The analysis method used is the Structural Equation Model - Partial Least Square with the help of the SmartPLS 4 application in testing the hypothesis. The results of this study indicate that first, Corporate social responsibility has a positive but insignificant relationship to tax avoidance. Second, Corporate social responsibility and the role of women's direction have an insignificant relationship to tax avoidance.